Post-Divorce Custody of Children According to Positive and Islamic Laws - Abd. Munim (Universitas Islam Sultan Agung, 2020)
The purpose of this study is to reveal and describe a more comprehensive understanding of post-divorce custody of children according to positive law and Islamic law.The research used in this research is a research in the category of literature (library research), while the approach method used in this research is the normative approach method, namely an approach based on the Koran and the Prophet's sunnah, including the interpretation of the verses. in the Koran, as well as a juridical approach, namely an approach based on legislation or disputes such as the compilation of Islamic law and jurisprudence. This research is descriptive-analytic, namely research that aims to develop data then analyzed and conclusions drawn.The results of the analysis show that in the Compilation of Islamic Law it is stated that the implementation of these obligations is a joint obligation between a husband (father) and wife (mother), because husband and wife are complementary parts, namely needing each other and mutual cooperation in living home life. the stairs and raising her kids. Therefore, a mother is considered more appropriate in carrying out the hadhanah because their female instincts are more suitable for caring for and educating children, and their patience in dealing with children's life problems is higher than that of a man. However, in terms of the cost of caring for the child, whatever form it takes, if it is really needed, it is the responsibility of the father that must be fulfilled.Keywords: custody; child; divorce; positive law; Islamic law